PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN GAJI KARYAWAN TERHADAP KEPUASAN KERJA DI PT.AYLA JAVA MANDIRA SUKOHARJO - Khotimah, Tita Nurul; Surendra, Arya (Universitas Of Surakarta, 2023)
This study aims to determine the effect of leadership, work environment, and employee salaries on job satisfaction at PT. Ayla Java Mandira. In this study the authors used a type of quantitative research. In this study the number of samples determined by researchers was 50 employees. using Non Probability Sampling, Saturated Sampling. In this study the data taken were primary data, namely by using a questionnaire in the form of a questionnaire and distributed to employees of PT. Ayla Java Mandira who were the research samples. the following: 1. Leadership Variables Leadership variables have a coefficient of 0.008 which is positive with a significance value of (0.856) 0.05. Based on these data, it can be concluded that the Leadership variable has no effect on Job Satisfaction of employees of PT. Ayla Java Mandira. 2. Work Environment Variables Leadership variables have a coefficient of 0.726 which is positive with a significance value of (0.000) 0.05. Based on these data, it can be concluded that the Work Environment variable influences the Job Satisfaction of employees of PT. Ayla Java Mandira. 3. Employee Salary Variable Leadership variable has a coefficient of 0.365 which is positive with a significance value of (0.000) 0.05. Based on these data, it can be concluded that the variable Employee Salary has an effect on Job Satisfaction of employees of PT. Ayla Java Mandira. The results of the F test found that the significance was 0.000 0.05 and the Fcount (164.794) Ftable (2.81). This shows that the three variables (Leadership, Employee Salary and Work Environment) simultaneously affect the Job Satisfaction of employees of PT. Ayla Java Mandira.